2014
DOI: 10.1080/01621459.2014.950735
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Species Sampling Priors With Latent Beta Reinforcements

Abstract: Many popular Bayesian nonparametric priors can be characterized in terms of exchangeable species sampling sequences. However, in some applications, exchangeability may not be appropriate. We introduce a novel and probabilistically coherent family of non-exchangeable species sampling sequences characterized by a tractable predictive probability function with weights driven by a sequence of independent Beta random variables. We compare their theoretical clustering properties with those of the Dirichlet Process a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…The HMM model is fit over a grid of values of K , and the model fit for each value of K is then assessed through a goodness-of-fit criterion, such as the deviance information criterion [64]. The second approach uses Bayesian non-parametrics [65, 66], which has the advantage of automatically learning the value of K but the disadvantage of the need to explore transdimensional parameter spaces, thus adding to the computational demands of the algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The HMM model is fit over a grid of values of K , and the model fit for each value of K is then assessed through a goodness-of-fit criterion, such as the deviance information criterion [64]. The second approach uses Bayesian non-parametrics [65, 66], which has the advantage of automatically learning the value of K but the disadvantage of the need to explore transdimensional parameter spaces, thus adding to the computational demands of the algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…In their simulation study of several of these approaches, they found no dominant method and suggested choosing among them based on the inferential goals. More recently, Airoldi et al (2014) provided a general family of nonexchangeable species sampling sequences dependent on the realizations of a set of latent variables.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we consider the Bayesian nonparametric approach introduced in Lijoi et al [24] and further investigated in Favaro et al [13] and Favaro et al [14]. Other recent contributions to species sampling problems in the Bayesian framework are, e.g., Navarrete et al [28], Zhang and Stern [33], Barger and Bunge [6], Bacallado et al [3], Lee et al [23], Airoldi et al [1] and Guindani et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recall that, due to the de Finetti representation theorem, X n is part of the exchangeable sequence (X i ) i≥1 with directing measure Π. Under the nonparametric framework (1), and with Π belonging to the class of Gibbs-type priors by Gnedin and Pitman [17], results in Lijoi et al [24] and Favaro et al [14] provide explicit posterior distributions for several features of an additional unobserved sample (X n+1 , . .…”
Section: Introductionmentioning
confidence: 99%